A Techno-Economic Viability Analysis of the Two-Axis Tracking Grid-Connected Photovoltaic Power System for 25 Selected Coastal Mediterranean Cities - Kassem, Y.; Gökçekuş, H.; Lagili, H. S. A. (Engineering, Technology & Applied Science Research, 2021)
Generating energy from renewable sources, particularly solar energy, offers significant benefits and achieves a more clean and sustainable development. In the present paper, the potential of developing a 4.2kW grid-connected rooftop two-axis tracking PV system in 25 selected coastal Mediterranean cities located in different Arabic countries is evaluated using RETScreen software. The proposed system is serving the basic household energy needs according to the load profile from monthly electrical bills. It is found that the proposed system produces about 8824kW annually, which helps to reduce CO2 emissions. Also, the average energy production cost is assumed to range from 0.0337 to 00.0475/kWh. It is concluded that the proposed system can provide an effective solution for energy poverty in developing regions with a very positive socio-economic and environmental impact. The small-scale grid-connected PV system will provide the domestic energy needs at a lower energy production cost than the electricity price grid-connected consumers pay. This study demonstrated that generating electricity from solar energy will help reduce the electricity tariff rates and the dependence on fossil fuels.